Perempuan dalam Lintasan Sejarah Tasawuf - Sururin Sururin (Ulumuna, 2010)
A widely presumption holds that Sufism is a male domain. The claim may be not totally misleading since many references that exist up to the present support this assumption. A great number of stories and scholarly works are dominated and authored by male sufis. Almost none of female sufi left a crucial legacy in the field, except the stories of female sufi piety narrated by male sufi scholars. However, this study challenges this assumption, contending that female sufis have played roles since the beginning of Islam up to the medieval periods. The study attempts to describe such roles. It also sheds light on their role in sufi organization (tarekat) up to the present time in Indonesia. The discussion starts by elucidating female sufi figures throghout the history of sufism in Islam and then the discussion of female sufis in Indonesia follows.